Disentangling endowment effect and the preferences for good deals in the presence of trade-in : an experimental analysis - Tan, Kwang Hui (2014)
The disparity between Willingness to Accept (WTA) and Willingness to Pay (WTP) is commonly explained by endowment effect, which describes pain-of-losing account. Recent literature has presented an alternative viewpoint that WTA-WTP disparity could be due to aversion to bad deals. However, there are no known literature that are able to disentangle these two effects. Our study presents a distinct factor that can affect the WTA-WTP disparity using the trade-in method. In a two-part experiment, we attempt to observe the changes in WTA for the loss of currently endowed goods in the presence of a trade-in option. Our results suggest that along with endowment effect and aversion to bad deals, an inclination towards good deals (good deals effect) is a factor that explains the further WTA-WTP disparity. We thus contribute to the current literature by extending another method to study WTA-WTP disparity.